Detection of Carbapenemase-Producing Acinetobacter baumannii in a Hospital - Takahashi, Ayako (American Society for Microbiology, 2000)
Acinetobacter baumannii strains resistant to both imipenem (IPM) and ceftazidime (CAZ) were isolated from 1994 through 1996 at Gunma University Hospital. Nine isolates from different inpatients were examined for carbapenem-hydrolyzing activity and for the carbapemase gene bla(IMP) by the PCR method. All nine isolates were carbapenemase-producing strains that hydrolyzed IPM and that harbored bla(IMP). The bla(IMP) gene was transmissible by conjugation to an IPM-susceptible recipient strain of A. baumannii and conferred resistance to IPM, CAZ, cefotaxime (CTX), ampicillin (AMP), and piperacillin (PIP). Either intermediate or high-level resistance to amikacin (AMK) was transferred from two and five strains, respectively, concomitantly with bla(IMP), and gentamicin (GEN) resistance was also transferred in one instance of high-level AMK resistance. Comparative examination of clinical isolates for resistance patterns to nine drugs, IPM, CAZ, CTX, aztreonam, AMP, PIP, AMK, GEN, and norfloxacin, in addition to pulsed-field gel electrophoresis patterns with NotI-digested genomic DNA, confirmed nosocomial transmission of infections involving carbapenemase-producing A. baumannii strains.